Anti-aging oxidation table tennis bat rubber and preparation method thereof
By using specific formulas and processes in table tennis racket rubber, the existing rubber is easily aging and hardened, and higher aging resistance and oxidation and wear resistance are achieved, extending the service life of the racket and improving the athletes' Competition experience.
Patent Information
- Application Number
- CN202411603896.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing table tennis racket rubber is prone to aging and hardening during long-term use or in harsh environments, resulting in performance degradation and wear, affecting the athlete's game experience.
Aging-resistant oxidation ping-pong racket rubber is used, and its formula includes natural rubber, styrene butadiene rubber, strong antioxidants, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and phthalic acid Butyl esters are prepared by specific drying, crushing, kneading and cross-linking processes.
The rubber remains smooth during long-term use, reducing wear and aging, extending the service life of the table tennis racket, and improving the athlete's batting quality and game experience.
Smart Images

Figure BDA0005129019710000171
Abstract
Description
Technical Field
[0001] The invention relates to the field of table tennis racket rubber materials, and in particular to an aging and oxidation resistant table tennis racket rubber and a preparation method thereof. Background Art
[0002] Table tennis is a popular sport worldwide, and table tennis rackets are an important tool for the game, and their performance directly affects the performance of athletes. The wear resistance and aging resistance of the table tennis racket rubber, as the part that is in direct contact with the ball, directly affect the performance and service life of the racket. Although the existing table tennis racket rubber materials have certain wear resistance and aging resistance, they are prone to aging and hardening after long-term use or placement in harsh environments, resulting in a decrease in racket performance, and wear and tear will occur after frequent use, affecting the athlete's game experience. Therefore, the development of an aging-resistant oxidation table tennis racket rubber and a preparation method thereof is of great significance for improving the performance of table tennis rackets. Summary of the invention
[0003] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide an aging-resistant and oxidation-resistant table tennis racket rubber and a preparation method thereof, which solves the problem that the existing table tennis racket rubber has poor aging-resistant and oxidation-resistant properties and wear-resistant properties, which easily leads to a decline in the performance of the table tennis racket and affects the athletes' game experience.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A table tennis racket rubber resistant to aging and oxidation, comprising the following components in parts by weight:
[0006] 32-56 parts of natural rubber, 28-42 parts of styrene-butadiene rubber, 2.1-6.5 parts of strong antioxidant, 11-21 parts of modified composite powder, 2-4 parts of di(2,4-dichlorobenzoyl) peroxide and 5-9 parts of butyl phthalate;
[0007] Wherein, the strong antioxidant is prepared by the following steps:
[0008] Step a1: tetraphenylmethane, concentrated sulfuric acid and concentrated nitric acid are added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of -10°C and a stirring rate of 400-500 r / min for 1-1.5 hours, and then the mixture is heated to 60-65°C and stirred for 8-10 hours. After the reaction is completed, the reaction product is adjusted to a pH of 5.5-6 with a sodium hydroxide solution, and then vacuum filtered. The filter cake is washed with anhydrous ethanol for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 2-3 hours to obtain an intermediate substance I;
[0009] The principle of the chemical reaction involved in step a1 is as follows:
[0010] Tetraphenylmethane undergoes nitration reaction under the conditions of concentrated sulfuric acid and concentrated nitric acid, which can introduce nitro groups on each benzene ring to obtain intermediate substance Ⅰ;
[0011] Step a2: add intermediate substance I, 10% palladium carbon and anhydrous tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and an introduction tube, introduce nitrogen to remove the air in the three-necked flask, then introduce hydrogen to maintain the pressure at 1.8-2.2 MPa, then stir the reaction at a temperature of 25-30° C. and a stirring rate of 400-500 r / min for 20-30 min, then heat to 65-70° C. and continue stirring the reaction for 2-3 h, after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate substance II;
[0012] The principle of the chemical reaction involved in step a2 is as follows:
[0013] The intermediate substance I is reacted with hydrogen to reduce the nitro group on the intermediate substance I to an amino group, thereby obtaining the intermediate substance II;
[0014] Step a3: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and chloroform to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 5-10 minutes at a temperature of 25-30° C. and a stirring rate of 400-500 r / min, then add thionyl chloride dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to 50-55° C. and the stirring reaction is continued for 4-5 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain an intermediate substance III;
[0015] The principle of the chemical reaction involved in step a3 is as follows:
[0016] Utilizing the reaction of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid with thionyl chloride, the carboxyl group on the 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is converted into an acyl chloride group, thereby enhancing its reactivity and obtaining intermediate substance III;
[0017] Step a4: add intermediate substance II, intermediate substance III and anhydrous acetonitrile to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, introduce nitrogen protection, add triethylamine solution dropwise while stirring at a temperature of 0-5°C and a stirring rate of 400-500r / min, and control the dropping rate to 1-2 drops / s until the pH is 9-10, then heat to 55-60°C and continue stirring the reaction for 20-25h. After the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then wash with sodium bicarbonate solution and hydrochloric acid solution for 3-5 times in sequence, then place in a vacuum drying oven, and dry at a temperature of 60-70°C for 8-10h to obtain a strong antioxidant;
[0018] The principle of the chemical reaction involved in step a4 is as follows:
[0019] By using the reaction between intermediate substance II and intermediate substance III, the amino group on intermediate substance II reacts with the acyl chloride group on intermediate substance III, thereby introducing a large amount of hindered phenol structure to obtain a strong antioxidant;
[0020] As a further solution of the present invention: the usage ratio of the tetraphenylmethane, concentrated sulfuric acid and concentrated nitric acid in step a1 is 10mmol:20-25mL:20-25mL; the mass fraction of the concentrated sulfuric acid is 98%, the mass fraction of the concentrated nitric acid is 68%, and the mass fraction of the sodium hydroxide solution is 25-35%.
[0021] As a further scheme of the present invention: the usage ratio of the intermediate substance I, 10% palladium carbon and anhydrous tetrahydrofuran in step a2 is 10 mmol: 0.15-0.2 g: 50-55 mL.
[0022] As a further solution of the present invention: the usage ratio of the 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, chloroform and thionyl chloride in step a3 is 10 mmol:50-55 mL:8-10 mL.
[0023] As a further scheme of the present invention: the usage ratio of the intermediate substance II, the intermediate substance III and anhydrous acetonitrile in step a4 is 10mmol:45-50mmol:100-120mL; the triethylamine solution in step a4 is a solution with a molar concentration of 0.2-0.25mol / L formed by dissolving triethylamine in anhydrous acetonitrile, the mass fraction of the sodium bicarbonate solution is 5-8%, and the mass fraction of the hydrochloric acid solution is 8-10%.
[0024] As a further solution of the present invention: the modified composite powder is prepared by the following steps:
[0025] Step b1: adding zirconium carbide powder and silicon carbide powder to anhydrous ethanol, ultrasonically dispersing for 15-20 minutes at an ultrasonic power of 250-350W, then adding to a ball mill, ball milling for 10-15 hours at a ball milling ratio of 3:1 and a rotation speed of 250-300r / min, then placing the ball milled slurry in a vacuum drying oven, drying at a temperature of 100-120°C for 4-5 hours, then crushing and placing in a mold, then heating to 1600-1800°C at a heating rate of 15-20°C / min and a pressure of 30-35Ma, then sintering for 1-2 hours, and then cooling to room temperature with the furnace to obtain a composite powder;
[0026] The principles involved in step b1 are as follows:
[0027] Through spheroidal graphite and sintering, the zirconium carbide powder and the silicon carbide powder are fully combined to form a composite powder having the excellent properties of both zirconium carbide powder and silicon carbide powder;
[0028] Step b2: Add the composite powder and ethanol solution to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 25-30 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min, then add the silane coupling agent KH560 and continue to stir and react for 25-30 minutes, then heat the temperature to reflux and continue to stir and react for 3-5 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, place the precipitate in a vacuum drying oven, and dry it at a temperature of 60-65°C for 4-5 hours to obtain a modified composite powder;
[0029] The principle of the chemical reaction involved in the process of step b2 is as follows:
[0030] The composite powder is modified by using silane coupling agent KH560. The siloxane groups on the silane coupling agent KH560 are hydrolyzed to form silanols, which can be condensed and grafted to the particle surface of the composite powder, making the composite powder less likely to agglomerate and able to be evenly distributed in the matrix material. The dispersion performance is greatly improved, which can achieve the best performance enhancement effect.
[0031] As a further solution of the present invention: the usage ratio of the zirconium carbide powder, silicon carbide powder and anhydrous ethanol in step b1 is 10g:1-2.5g:150-180mL.
[0032] As a further solution of the present invention: the usage ratio of the composite powder, ethanol solution and silane coupling agent KH560 in step b2 is 2g:40-45mL:1.5-3.5mL; the volume fraction of the ethanol solution is 85-95%.
[0033] As a further solution of the present invention: a method for preparing an aging-resistant and oxidized table tennis racket rubber comprises the following steps:
[0034] Step 1: weigh 32-56 parts of natural rubber, 28-42 parts of styrene-butadiene rubber, 2.1-6.5 parts of strong antioxidant, 11-21 parts of modified composite powder, 2-4 parts of di(2,4-dichlorobenzoyl) peroxide and 5-9 parts of butyl phthalate according to weight parts, and set aside;
[0035] Step 2: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at a temperature of 60-65° C. for 2-3 hours, and then crushing them to obtain mixed rubber powder;
[0036] Step 3: Add the mixed rubber powder, strong antioxidant, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 150-160°C for 30-35 minutes. Then, calender it to make a film of the required thickness, and then form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
[0037] Beneficial effects of the present invention:
[0038] A kind of aging-resistant oxidation table tennis racket rubber of the present invention and preparation method thereof, by drying natural rubber and styrene-butadiene rubber, then crushing, obtain mixed rubber powder, add mixed rubber powder, strong antioxidant, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate in a mixer, mix evenly, then heat-treat the rubber after mixing and crosslink, then calender, make a film of required thickness, then cut into the shape of table tennis racket rubber by mold forming, obtain aging-resistant oxidation table tennis racket rubber; by the preparation method of the present invention, the obtained table tennis racket rubber has excellent aging-resistant oxidation performance and wear resistance, and during long-term use, the rubber surface remains smooth, without obvious wear and aging phenomenon, effectively prolonging the service life of table tennis racket. In addition, the rubber has good elasticity and touch feeling, can improve the batting quality and competition experience of athletes, and is of great significance for improving the performance of table tennis racket. At the same time, the preparation method is simple in process, easy to realize industrial production, and has a wide range of application prospects.
[0039] In the process of preparing the aging and oxidation resistant table tennis racket rubber, a strong antioxidant is first prepared. The strong antioxidant contains a large number of benzene rings, which give it excellent mechanical properties. It also contains a large number of hindered phenol structures. The hydrogen atoms on the hydroxyl groups in the hindered phenol structure are easily detached from the original molecular structure and are easily combined with free radicals generated during the aging and oxidation process of the rubber, causing it to lose its original activity, inhibiting the continuation of the aging and oxidation process, and giving it excellent aging and oxidation resistance, so that the table tennis racket rubber is not prone to aging during use, ensuring the excellent performance of the table tennis racket rubber and maintaining a good batting experience for a long time;
[0040] In the process of preparing aging-resistant oxidation table tennis racket rubber, a modified composite powder is also prepared. Zirconium carbide has a series of excellent properties such as high hardness, high thermal conductivity, high elastic modulus and excellent thermal shock resistance. Silicon carbide ceramics have a series of excellent properties such as high corrosion resistance, high wear resistance, high strength, high hardness, high specific modulus and good thermal conductivity. The combination of the two has comprehensive excellent performance, which can improve the mechanical properties and wear resistance of the table tennis racket rubber, making the table tennis racket rubber have long-lasting excellent performance. The composite powder modified with silane coupling agent KH560 is not easy to agglomerate and can be evenly distributed in the table tennis racket rubber, which can have the best performance enhancement effect on the table tennis racket rubber. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Embodiment 1:
[0043] This embodiment is a method for preparing an aging-resistant and oxidized table tennis racket rubber, comprising the following steps:
[0044] Step S1: 10 mmol of tetraphenylmethane, 20 mL of 98% concentrated sulfuric acid and 20 mL of 68% concentrated nitric acid were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen was introduced for protection. The mixture was stirred at -10°C and a stirring rate of 400 r / min for 1 hour, and then the mixture was heated to 60°C and stirred for 8 hours. After the reaction was completed, the reaction product was adjusted to a pH of 5.5 with a 25% sodium hydroxide solution, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at 60°C for 2 hours to obtain an intermediate substance I.
[0045] Step S2: 10 mmol of intermediate substance I, 0.15 g of 10% palladium carbon and 50 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and an introduction tube, and nitrogen was introduced to remove the air in the three-necked flask, and then hydrogen was introduced to maintain the pressure at 1.8 MPa, and then the reaction was stirred at a temperature of 25° C. and a stirring rate of 400 r / min for 20 min, and then the temperature was raised to 65° C. and the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate substance II;
[0046] Step S3: 10 mmol 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 50 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 5 min, and then 8 mL thionyl chloride was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to 50° C. and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate substance III;
[0047] Step S4: 10 mmol of intermediate substance II, 45 mmol of intermediate substance III and 100 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen protection is introduced. Under the conditions of a temperature of 0°C and a stirring rate of 400 r / min, a triethylamine solution with a molar concentration of 0.2 mol / L formed by dissolving triethylamine in anhydrous acetonitrile is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s until the pH is 9, and then the temperature is raised to 55°C and the stirring reaction is continued for 20 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then it is washed three times with a sodium bicarbonate solution with a mass fraction of 5% and a hydrochloric acid solution with a mass fraction of 8%, and then placed in a vacuum drying oven and dried at a temperature of 60°C for 8 hours to obtain a strong antioxidant;
[0048] Step S5: 10 g zirconium carbide powder and 1 g silicon carbide powder are added to 150 mL anhydrous ethanol, ultrasonically dispersed for 15 min under the condition of ultrasonic power of 250 W, then added to a ball mill, ball milled for 10 h under the condition of ball milling ratio of 3:1 and rotation speed of 250 r / min, then the ball milled slurry is placed in a vacuum drying oven, dried at a temperature of 100 ° C for 4 h, then crushed and placed in a mold, then heated to 1600 ° C at a heating rate of 15 ° C / min and a pressure of 30 Ma, then sintered for 1 h, and then cooled to room temperature with the furnace to obtain a composite powder;
[0049] Step S6: 2 g of the composite powder and 40 mL of an ethanol solution with a volume fraction of 85% were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 25 min, and then 1.5 mL of a silane coupling agent KH560 was added and the stirring reaction was continued for 25 min, and then the mixture was heated to reflux and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 60° C. for 4 h to obtain a modified composite powder;
[0050] Step S7: weigh 32 parts of natural rubber, 28 parts of styrene-butadiene rubber, 2.1 parts of strong antioxidant, 11 parts of modified composite powder, 2 parts of di(2,4-dichlorobenzoyl) peroxide and 5 parts of butyl phthalate according to weight parts, and set aside;
[0051] Step S8: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at 60° C. for 2 h, and then crushing them to obtain mixed rubber powder;
[0052] Step S9: Add the mixed rubber powder, strong antioxidant, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 150°C for 30 minutes. Then, calender it to make a film of the required thickness, and then form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
[0053] Embodiment 2:
[0054] This embodiment is a method for preparing an aging-resistant and oxidized table tennis racket rubber, comprising the following steps:
[0055] Step S1: 10 mmol of tetraphenylmethane, 22 mL of 98% concentrated sulfuric acid and 22 mL of 68% concentrated nitric acid were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen was introduced for protection. The mixture was stirred at -10°C and a stirring rate of 450 r / min for 1.2 h, and then the mixture was heated to 62°C and stirred for 9 h. After the reaction was completed, the reaction product was adjusted to a pH of 5.8 with a 30% sodium hydroxide solution, and then vacuum filtered. The filter cake was washed with anhydrous ethanol 4 times, and then placed in a vacuum drying oven and dried at 62°C for 2.5 h to obtain an intermediate substance I.
[0056] Step S2: 10 mmol of intermediate substance I, 0.18 g of 10% palladium carbon and 52 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and an introduction tube, and nitrogen was introduced to remove the air in the three-necked flask, and then hydrogen was introduced to maintain the pressure at 2.0 MPa, and then the reaction was stirred at a temperature of 28° C. and a stirring rate of 450 r / min for 25 min, and then the temperature was raised to 68° C. and the stirring reaction was continued for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate substance II;
[0057] Step S3: 10 mmol 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 52 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The reaction was stirred for 8 min at a temperature of 28° C. and a stirring rate of 450 r / min. Then, 9 mL thionyl chloride was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to 52° C. and the stirring reaction was continued for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate substance III;
[0058] Step S4: 10 mmol of intermediate substance II, 48 mmol of intermediate substance III and 110 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen protection is introduced. Under the conditions of a temperature of 2° C. and a stirring rate of 450 r / min, a triethylamine solution with a molar concentration of 0.22 mol / L formed by dissolving triethylamine in anhydrous acetonitrile is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s until the pH is 9.5, and then the temperature is raised to 58° C. and the stirring reaction is continued for 22 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then it is washed 4 times with a sodium bicarbonate solution with a mass fraction of 6.5% and a hydrochloric acid solution with a mass fraction of 9%, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 9 hours to obtain a strong antioxidant;
[0059] Step S5: 10 g zirconium carbide powder and 1.7 g silicon carbide powder are added to 165 mL anhydrous ethanol, ultrasonically dispersed for 18 min at an ultrasonic power of 300 W, then added to a ball mill, ball milled for 12 h at a ball milling ratio of 3:1 and a rotation speed of 275 r / min, then the ball milled slurry is placed in a vacuum drying oven, dried at a temperature of 110° C. for 4.5 h, then crushed and placed in a mold, then heated to 1700° C. at a heating rate of 18° C. / min and a pressure of 32 Ma, then sintered for 1.5 h, and then cooled to room temperature with the furnace to obtain a composite powder;
[0060] Step S6: 2 g of the composite powder and 42 mL of an ethanol solution with a volume fraction of 90% were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred at 28° C. and a stirring rate of 450 r / min for 28 min, and then 2.5 mL of a silane coupling agent KH560 was added and the mixture was stirred for 28 min, and then the mixture was heated to reflux and stirred for 4 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at 62° C. for 4.5 h to obtain a modified composite powder;
[0061] Step S7: weigh 44 parts of natural rubber, 35 parts of styrene-butadiene rubber, 4.3 parts of strong antioxidant, 16 parts of modified composite powder, 3 parts of di(2,4-dichlorobenzoyl)peroxide and 7 parts of butyl phthalate according to weight parts, and set aside;
[0062] Step S8: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at 62° C. for 2.5 h, and then crushing them to obtain mixed rubber powder;
[0063] Step S9: Add the mixed rubber powder, strong antioxidant, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 155°C for 32 minutes. Then, calender it to make a film of the required thickness, and then form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
[0064] Embodiment 3:
[0065] This embodiment is a method for preparing an aging-resistant and oxidized table tennis racket rubber, comprising the following steps:
[0066] Step S1: 10 mmol of tetraphenylmethane, 25 mL of 98% concentrated sulfuric acid and 25 mL of 68% concentrated nitric acid were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen was introduced for protection. The mixture was stirred at -10°C and a stirring rate of 500 r / min for 1.5 h, and then the mixture was heated to 65°C and stirred for 10 h. After the reaction was completed, the reaction product was adjusted to a pH of 6 with a 35% sodium hydroxide solution, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at 65°C for 3 h to obtain an intermediate substance I.
[0067] Step S2: 10 mmol of intermediate substance I, 0.2 g of 10% palladium carbon and 55 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and an introduction tube, and nitrogen was introduced to remove the air in the three-necked flask, and then hydrogen was introduced to maintain the pressure at 2.2 MPa, and then the reaction was stirred at a temperature of 30° C. and a stirring rate of 500 r / min for 30 min, and then the temperature was raised to 70° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate substance II;
[0068] Step S3: 10 mmol 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 55 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 10 min, and then 10 mL thionyl chloride was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the temperature was raised to 55° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate substance III;
[0069] Step S4: 10 mmol of intermediate substance II, 50 mmol of intermediate substance III and 120 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen protection is introduced. Under the conditions of a temperature of 5° C. and a stirring rate of 500 r / min, a triethylamine solution with a molar concentration of 0.25 mol / L formed by dissolving triethylamine in anhydrous acetonitrile is added dropwise while stirring, and the dropping rate is controlled to 2 drops / s until the pH is 10, and then the temperature is raised to 60° C. and the stirring reaction is continued for 25 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then it is washed 5 times with a sodium bicarbonate solution with a mass fraction of 8% and a hydrochloric acid solution with a mass fraction of 10%, and then placed in a vacuum drying oven and dried at a temperature of 70° C. for 10 hours to obtain a strong antioxidant;
[0070] Step S5: 10 g zirconium carbide powder and 2.5 g silicon carbide powder are added to 180 mL anhydrous ethanol, ultrasonically dispersed for 20 min at an ultrasonic power of 350 W, then added to a ball mill, ball milled for 15 h at a ball milling ratio of 3:1 and a rotation speed of 300 r / min, then the ball milled slurry is placed in a vacuum drying oven, dried at a temperature of 120° C. for 5 h, then crushed and placed in a mold, then heated to 1800° C. at a heating rate of 20° C. / min and a pressure of 35 Ma, then sintered for 2 h, and then cooled to room temperature with the furnace to obtain a composite powder;
[0071] Step S6: 2 g of the composite powder and 45 mL of an ethanol solution with a volume fraction of 95% were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 30 min, and then 3.5 mL of a silane coupling agent KH560 was added and the stirring reaction was continued for 30 min, and then the mixture was heated to reflux and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 65° C. for 5 h to obtain a modified composite powder;
[0072] Step S7: weigh 56 parts of natural rubber, 42 parts of styrene-butadiene rubber, 6.5 parts of strong antioxidant, 21 parts of modified composite powder, 4 parts of di(2,4-dichlorobenzoyl) peroxide and 9 parts of butyl phthalate according to weight parts, and set aside;
[0073] Step S8: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at 65° C. for 3 h, and then crushing them to obtain mixed rubber powder;
[0074] Step S9: Add the mixed rubber powder, strong antioxidant, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 160°C for 35 minutes. Then, calender it to make a film of the required thickness, and then form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
[0075] Comparative Example 1:
[0076] This comparative example is a method for preparing an aging-resistant and oxidized table tennis racket rubber, comprising the following steps:
[0077] Step S1: weigh 56 parts of natural rubber, 42 parts of styrene-butadiene rubber, 10766.5 parts of antioxidant, 4 parts of di(2,4-dichlorobenzoyl)peroxide and 9 parts of butyl phthalate according to weight parts, and set aside;
[0078] Step S2: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at 65° C. for 3 h, and then crushing them to obtain mixed rubber powder;
[0079] Step S3: Add the mixed rubber powder, antioxidant 1076, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 160°C for 35 minutes. Then, calender it to make a film of the required thickness. Then, form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
[0080] Comparative Example 2:
[0081] This comparative example is a method for preparing an aging-resistant and oxidized table tennis racket rubber, comprising the following steps:
[0082] Step S1: 10 mmol of tetraphenylmethane, 25 mL of 98% concentrated sulfuric acid and 25 mL of 68% concentrated nitric acid were added to a three-necked flask equipped with a stirrer, a thermometer and a nitrogen inlet tube, and nitrogen was introduced for protection. The mixture was stirred at -10°C and a stirring rate of 500 r / min for 1.5 h, and then the mixture was heated to 65°C and stirred for 10 h. After the reaction was completed, the reaction product was adjusted to a pH of 6 with a 35% sodium hydroxide solution, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at 65°C for 3 h to obtain an intermediate substance I.
[0083] Step S2: 10 mmol of intermediate substance I, 0.2 g of 10% palladium carbon and 55 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and an introduction tube, and nitrogen was introduced to remove the air in the three-necked flask, and then hydrogen was introduced to maintain the pressure at 2.2 MPa, and then the reaction was stirred at a temperature of 30° C. and a stirring rate of 500 r / min for 30 min, and then the temperature was raised to 70° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate substance II;
[0084] Step S3: 10 mmol 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 55 mL chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 10 min, and then 10 mL thionyl chloride was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the temperature was raised to 55° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate substance III;
[0085] Step S4: 10 mmol of intermediate substance II, 50 mmol of intermediate substance III and 120 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube and a constant pressure dropping funnel, and nitrogen protection is introduced. Under the conditions of a temperature of 5° C. and a stirring rate of 500 r / min, a triethylamine solution with a molar concentration of 0.25 mol / L formed by dissolving triethylamine in anhydrous acetonitrile is added dropwise while stirring, and the dropping rate is controlled to 2 drops / s until the pH is 10, and then the temperature is raised to 60° C. and the stirring reaction is continued for 25 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then it is washed 5 times with a sodium bicarbonate solution with a mass fraction of 8% and a hydrochloric acid solution with a mass fraction of 10%, and then placed in a vacuum drying oven and dried at a temperature of 70° C. for 10 hours to obtain a strong antioxidant;
[0086] Step S5: weigh 56 parts of natural rubber, 42 parts of styrene-butadiene rubber, 6.5 parts of a strong antioxidant, 4 parts of di(2,4-dichlorobenzoyl)peroxide and 9 parts of butyl phthalate according to weight parts for later use;
[0087] Step S6: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at 65° C. for 3 h, and then crushing them to obtain mixed rubber powder;
[0088] Step S7: Add the mixed rubber powder, strong antioxidant, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 160°C for 35 minutes. Then, calender it to make a film of the required thickness, and then form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
[0089] Comparative Example 3:
[0090] This comparative example is a method for preparing an aging-resistant oxidation table tennis racket rubber, comprising the following steps:
[0091] Step S1: 10 g zirconium carbide powder and 2.5 g silicon carbide powder are added to 180 mL anhydrous ethanol, ultrasonically dispersed for 20 min at an ultrasonic power of 350 W, then added to a ball mill, ball milled for 15 h at a ball milling ratio of 3:1 and a rotation speed of 300 r / min, then the ball milled slurry is placed in a vacuum drying oven, dried at a temperature of 120° C. for 5 h, then crushed and placed in a mold, then heated to 1800° C. at a heating rate of 20° C. / min and a pressure of 35 Ma, then sintered for 2 h, and then cooled to room temperature with the furnace to obtain a composite powder;
[0092] Step S2: 2 g of composite powder and 45 mL of 95% ethanol solution by volume were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 30 min, then 3.5 mL of silane coupling agent KH560 was added and the stirring reaction was continued for 30 min, then the temperature was raised to reflux and the stirring reaction was continued for 5 h, after the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged, and the precipitate was placed in a vacuum drying oven and dried at a temperature of 65° C. for 5 h to obtain a modified composite powder;
[0093] Step S3: weigh 56 parts of natural rubber, 42 parts of styrene-butadiene rubber, 10766.5 parts of antioxidant, 21 parts of modified composite powder, 4 parts of di(2,4-dichlorobenzoyl)peroxide and 9 parts of butyl phthalate according to weight parts, and set aside;
[0094] Step S4: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at 65° C. for 3 h, and then crushing them to obtain mixed rubber powder;
[0095] Step S5: Add the mixed rubber powder, antioxidant 1076, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 160°C for 35 minutes. Then, calender it to make a film of the required thickness, and then form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
[0096] The performance of the aging-resistant oxidation table tennis racket rubbers in Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in the following table:
[0097]
[0098] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be known that the use of the homemade strong antioxidants and modified composite powders of the present application can comprehensively improve the mechanical properties, aging and oxidation resistance, and wear resistance of the table tennis racket rubber. Among them, the strong antioxidants can significantly improve the aging and oxidation resistance of the table tennis racket rubber, and the modified composite powders can significantly improve the mechanical properties and wear resistance of the table tennis racket rubber.
[0099] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0100] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A table tennis racket rubber resistant to aging and oxidation, characterized in that: It includes the following components by weight: 32-56 parts of natural rubber, 28-42 parts of styrene-butadiene rubber, 2.1-6.5 parts of strong antioxidant, 11-21 parts of modified composite powder, 2-4 parts of di(2,4-dichlorobenzoyl) peroxide and 5-9 parts of butyl phthalate; Wherein, the strong antioxidant is prepared by the following steps: Step a1: Tetraphenylmethane, concentrated sulfuric acid and concentrated nitric acid are stirred for reaction. After the reaction is completed, the pH of the reaction product is adjusted with a sodium hydroxide solution, and then vacuum filtered, and the filter cake is washed and dried to obtain an intermediate substance I; Step a2: Add intermediate substance I, 10% palladium carbon and anhydrous tetrahydrofuran into a three-necked flask, then introduce hydrogen gas for stirring reaction, cool the reaction product after the reaction is completed, then vacuum filter, and rotary evaporate the filtrate to obtain intermediate substance II; Step a3: stirring 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and chloroform for reaction, then adding thionyl chloride dropwise while stirring, and continuing to stir the reaction after the addition is complete. After the reaction is completed, the reaction product is cooled and then rotary evaporated to obtain an intermediate substance III; Step a4: Add intermediate substance II, intermediate substance III and anhydrous acetonitrile into a three-necked flask, then add triethylamine solution dropwise while stirring, and then stir to react. After the reaction is completed, cool the reaction product, then rotary evaporate, wash and dry to obtain a strong antioxidant.
2. The aging-resistant oxidation table tennis racket rubber according to claim 1, characterized in that: The usage ratio of the tetraphenylmethane, concentrated sulfuric acid and concentrated nitric acid in step a1 is 10mmol:20-25mL:20-25mL; the mass fraction of the concentrated sulfuric acid is 98%, the mass fraction of the concentrated nitric acid is 68%, and the mass fraction of the sodium hydroxide solution is 25-35%.
3. The aging-resistant oxidation table tennis racket rubber according to claim 1, characterized in that: The usage ratio of the intermediate substance I, 10% palladium carbon and anhydrous tetrahydrofuran in step a2 is 10 mmol: 0.15-0.2 g: 50-55 mL.
4. The aging-resistant oxidation table tennis racket rubber according to claim 1, characterized in that: The usage ratio of the 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, chloroform and thionyl chloride in step a3 is 10 mmol:50-55 mL:8-10 mL.
5. The aging-resistant oxidation table tennis racket rubber according to claim 1, characterized in that: The usage ratio of the intermediate substance II, the intermediate substance III and anhydrous acetonitrile in step a4 is 10mmol:45-50mmol:100-120mL; the triethylamine solution in step a4 is a solution with a molar concentration of 0.2-0.25mol / L formed by dissolving triethylamine in anhydrous acetonitrile.
6. The aging-resistant oxidation table tennis racket rubber according to claim 1, characterized in that: The modified composite powder is prepared by the following steps: Step b1: ultrasonically dispersing zirconium carbide powder and silicon carbide powder, then ball milling, drying, crushing, placing in a mold for sintering, and then cooling in a furnace to obtain a composite powder; Step b2: The composite powder and ethanol solution are stirred for reaction, and then the silane coupling agent KH560 is added and the stirring reaction is continued. After the reaction is completed, the reaction product is cooled, centrifuged, and the precipitate is dried to obtain a modified composite powder.
7. The aging-resistant oxidation table tennis racket rubber according to claim 6, characterized in that: The usage ratio of the zirconium carbide powder, silicon carbide powder and anhydrous ethanol in step b1 is 10g:1-2.5g:150-180mL.
8. The aging-resistant oxidation table tennis racket rubber according to claim 6, characterized in that: The usage ratio of the composite powder, ethanol solution and silane coupling agent KH560 in step b2 is 2g:40-45mL:1.5-3.5mL; the volume fraction of the ethanol solution is 85-95%.
9. A method for preparing an aging-resistant and oxidative table tennis racket rubber, characterized in that: The following steps are involved: Step 1: weigh 32-56 parts of natural rubber, 28-42 parts of styrene-butadiene rubber, 2.1-6.5 parts of strong antioxidant, 11-21 parts of modified composite powder, 2-4 parts of di(2,4-dichlorobenzoyl) peroxide and 5-9 parts of butyl phthalate according to weight parts, and set aside; Step 2: placing the natural rubber and styrene-butadiene rubber in a vacuum drying oven, drying them at a temperature of 60-65° C. for 2-3 hours, and then crushing them to obtain mixed rubber powder; Step 3: Add the mixed rubber powder, strong antioxidant, modified composite powder, di(2,4-dichlorobenzoyl) peroxide and butyl phthalate into a mixer and mix them evenly. Then, place the mixed rubber in a vacuum drying oven and cross-link it at a temperature of 150-160°C for 30-35 minutes. Then, calender it to make a film of the required thickness, and then form it through a mold and cut it into the shape of a table tennis racket rubber to obtain an aging-resistant and oxidation-resistant table tennis racket rubber.
Citation Information
Cited By
Anti-aging compound additive for polyethylene weather-resistant film and preparation method of anti-aging compound additive
CN120329614A
Anti-aging elastic composite rubber for table tennis bats and preparation method of anti-aging elastic composite rubber
CN120757880A
Anti-aging elastic composite rubber for table tennis bat and preparation method thereof
CN120757880B